2004
DOI: 10.1177/0091270004268044
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Does Not Have a Clinically Significant Pharmacokinetic Interaction With Fenofibrate in Humans

Abstract: Simvastatin and fenofibrate are both commonly used lipid-regulating agents with distinct mechanisms of action, and their coadministration may be an attractive treatment for some patients with dyslipidemia. A 2-period, randomized, open-label, crossover study was conducted in 12 subjects to determine if fenofibrate and simvastatin are subject to a clinically relevant pharmacokinetic interaction at steady state. In treatment A, subjects received an 80-mg simvastatin tablet in the morning for 7 days. In treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 25 publications
3
60
1
Order By: Relevance
“…[43][44][45] By contrast, co-administration of fenofibrate and a range of commonly prescribed statins does not appear to influence the pharmacokinetics of the statin significantly ( figure 4). [46][47][48][49] These data indicate that fenofibrate would be the preferred fibrate for combination with a statin, a view confirmed by a recent consensus review of fibrate safety. 50 …”
Section: Combination Therapymentioning
confidence: 68%
“…[43][44][45] By contrast, co-administration of fenofibrate and a range of commonly prescribed statins does not appear to influence the pharmacokinetics of the statin significantly ( figure 4). [46][47][48][49] These data indicate that fenofibrate would be the preferred fibrate for combination with a statin, a view confirmed by a recent consensus review of fibrate safety. 50 …”
Section: Combination Therapymentioning
confidence: 68%
“…Such effective concentrations are similar to the plasma concentrations of simvastatin after the oral administration. 32 However, application of 1 mol/L simvastatin 10 minutes before and during stimulation with 1 U/mL thrombin had no effect on the thrombin-induced [Ca 2ϩ ] i elevation (data not shown). The similar attenuation of the thrombin-induced [Ca 2ϩ ] i elevation was observed with fluvastatin at a similar concentration range (data not shown).…”
Section: Long-term Treatment With Simvastatin Attenuated the Thrombinmentioning
confidence: 87%
“…Smaller changes in statin AUC (1.25-to 2-fold) were observed for rosuvastatin (Schneck et al, 2004) and pitavastatin (Mathew et al, 2004). A similar pharmacokinetic interaction has not been observed with fluvastatin (Spence et al, 1995) and, except for a metabolite of pravastatin (Pan et al, 2000), is generally not observed during coadministration of statins with other fibrates (fenofibrate or bezafibrate) (Kyrklund et al, 2001;Martin et al, 2003;Bergman et al, 2004). The relative potential for gemfibrozil to have a pharmacokinetic drug-drug interaction with atorvastatin was, however, until recently, not known (Backman et al, 2005;Whitfield et al, 2005).…”
mentioning
confidence: 78%